Ion beam treatment of polymers : application aspects from medicine to space - Kondyurin, A. V.; Bilek, Marcela (Elsevier insights., 2015)
Ion Beam Treatment of Polymers, Second Edition presents the results of polymer investigations and technique development in the field of polymer modification by high-energy ion beams. It shows how to use ion beam equipment in the polymer industry, as well as how to use it to produce new polymer materials. The authors, scientists and researchers active in the field, provide analysis and data from their work, and give an overview of related work by others. The authors focus on wetting, adhesion, hardness, chemical activity, environmental stability, biocompatibility, new synthesis methods, and sp.